STABILITY OF LIPASE ENZYME IN THE SYNTHESIS OF MONOACYLGLYCEROL A DERIVATIVE VEGETABLE OIL PRODUCT - Prima Luna (Widyariset, 2012)
Nowadays, the biotechnologically production of products using enzymes has received great considerationbecause the trend towards ecologically acceptable processes or environmentally safer. The employment of lipaseas a biocatalyst in the synthesis of monoacylgliserol (MAG) allows mild reaction conditions and easy recoveryof glycerol without purification or chemical waste production. Biocatalyst in this study was commercially immobilizedlipase from Candida antarctica. Aim of this study was to investigate the stability of commercially lipaseimmobilized enzyme in the synthesis of MAG, to understand the correlation between parameters, and to estimatethe half-life of enzyme activity. Immobilized lipase enzyme was employed in the synthesis of MAG, respectively.The re-use of this enzyme has given importance information for oil and fat’s biotechnological industries. Based onthe research results, the composition of MAG for 10 times reaction, respectively, decreased 7%, while the MAG’syield and the number of products decreased 16%. The correlation between the composition of the MAG and theyield were strong and in the same direction with r = 0,812. The half-life of immobilized lipase enzyme activity inthis study was estimated 30 times in the MAG synthesis‘s cycle due to the composition of MAGs.